Seminal cyclooxygenase relationship with oxidative stress in infertile oligoasthenoteratozoospermic men with varicocele. (23rd April 2015) - Mostafa, T.; Rashed, L.; Taymour, M.
Summary: This study aimed to assess the relation of seminal cyclooxygenase COX‐1, COX‐2 with oxidative stress in infertile oligoasthenoteratozoospermic (OAT) men with varicocele (Vx). In all, 128 men were allocated into fertile men, fertile men with Vx, infertile OAT men without Vx and infertile OAT men with Vx. They were subjected to history taking, clinical examination and semen analysis. Also, seminal COX‐1, COX‐2, malondialdehyde (MDA) and glutathione peroxidase (GPx) were estimated. Mean levels of seminal COX‐1, COX‐2 were over‐expressed, the mean level of seminal MDA was significantly increased, and the mean level of seminal GPx was significantly decreased in infertile OAT men with Vx compared with other groups. Seminal COX‐1 and COX‐2 were over‐expressed in cases with Vx grade III compared with Vx grades I, II cases and in cases with bilateral Vx compared with unilateral Vx. There was significant negative correlation between seminal COX‐1 and COX‐2 with sperm concentration, sperm motility, sperm normal morphology, seminal GPx and significant positive correlation with seminal MDA. It is concluded that seminal COX‐1 and COX‐2 are over‐expressed in infertile OAT men with Vx compared with fertile men with/without and infertile OAT men without Vx being associated with oxidative stress, Vx grade and Vx laterality.